and its Spelling Trap: Neither Mochica nor Quingnam but Quechumaran - Cerrón-Palomino, Rodolfo (2020)
The Latin digraph <ch>, used in the spelling of Old Castilian in the notation of words of Greek origin, remained in force in modern Castilian until the middle of the 17th century. It should not be surprising then that it has been used with a value of /k/, sporadically, to record voices of American origin, particularly in the Andean toponymy. In these cases, its /k/ value interpretation has presented no major problems, since the writing of the place names involved was supported by their pronunciation, verifiable in the language of origin. However, when the place name ceased to have such support, because it was registered in a territory other than that of the language of origin, it was prone to being distorted in form and meaning, because it was interpreted as a local designation. This situation became even worse in contexts devoid of sufficient linguistic information. In such cases, the place names registered <ch> with were ambiguous in their phonic interpretation, since they could be read as in Spanish, with a value of /č/, or as in Latin, with a value of /k/, such as Nebrija feared, as can be seen in our quotation. In this way, the erratic reading of the mentioned spelling only contributed to the etymological obscuring of the name. In this note, we will demonstrate that this is precisely what happened with the well-known Peruvian northern coast place name, <Chanchán>.